Living, Caring, Learning - Building family relationships in haemophilia care - Shoemark Robyn (The Journal of Haemophilia Practice)
With over 35 years’ experience of paediatric nursing, almost half of which she has spent in haemophilia care, Robyn reflects on the importance of taking a family-focused approach and engaging with parents and caregivers. She describes her experience of providing care for a family with two boys with severe haemophilia A and inhibitors, and how listening to and working closely with the parents enabled good outcomes. Robyn points to the central role of nursepatient relationship in haemophilia care but highlights the importance of ensuring that this close therapeutic relationship remains professional.